Implementasi Tanda Tangan Digital untuk Meningkatkan Efisiensi Administrasi Anggota Pramuka Saka Wira Kartika di Kodim 0610/Sumedang - Daffa Fadhlurohman; Yasri; Iim Abdurrohim (Universitas Kebangsaan Republik Indonesia, 2025)
Membership administration in Scout organizations is still mostly conducted manually, including member data recording, membership card (KTA) issuance, and announcement distribution. Manual processes often lead to issues such as delays in data collection, difficulties in searching for information, and the risk of document loss. Therefore, a digital system is required to manage membership administration more efficiently and securely. This research produces a Web-Based Scout Membership Administration System, developed using Node.js, Express, and Prisma ORM on the backend, and React.js with Tailwind CSS on the frontend. The system provides main features such as member registration and biodata management, KTA issuance in PDF format with an embedded QR Code, member data validation by the administrator, and announcement management. To enhance security, each KTA is embedded with a digital signature using the Ed25519 algorithm, allowing the authenticity of the data to be verified through QR Code scanning. The testing results show that this system is able to simplify the administrator’s tasks in validating and managing member data, while also providing convenience for members in accessing information and obtaining their KTA quickly. The implementation of digital signatures ensures data integrity and security, making the administrative process more effective, efficient, and reliable.